A Greater Distance between the Readers and the Recounted Story in Salvatore Besso’s Travel Book:: The Function of the Picture Postcards - Silapavithayadilok, Panita (Journal of Letters, 2024)
This article analyses the scanned picture postcards in Salvatore Besso’s travel book with the aim to point out how they assume a crucial role in changing the main theme of the narrative on Siam in this book. From two main themes that run along together in the written narrative, exotism of Siamese culture and the recognition that Siam gained from Western nations, the scanned picture postcards lead the readers to focus particularly, if not only, on the first theme. This article seeks to shed more light to the significance of intermedial perspective in delving into subtle motives in cultural encounters. The intermediality at work in this study concerns the interaction between photographs and words that represents the interaction between Western culture as the content creator/audience and Siamese culture as the created content.